Microstructure and Material Properties of LENS Fabricated Ti-6Al-4V Components (R&D Journal, 2018)
Cylindrical components of dimensions 15 mm in diameter and 11 mm in height were laser printed by additive manufacturing using a LENS™ system. Process parameters used in layer by layer build-ups showed that energy densities in the range of 200 – 300 J/mm3 were sufficient to produce adequate builds with improved physical structures and mechanical properties of Ti-6Al-4V ELI alloy, and subsequently used to produce tensile specimen that showed encouraging yield and tensile strengths in excess of 900 MPa. An approach to estimating the achievable tensile properties is proposed and investigated against experimental results as a means of identifying parameters to be used in studies aimed at tailoring mechanical properties of materials.